Study of Welfare Level of Fisherman Community in Alo Village, Rainis District, Talaud Islands Regency - Toesan, Fritwin; Manoppo, Lefrand; Kayadoe, Mariana E (Sam Ratulangi University, 2023)
Talaud Islands Regency is a maritime area with a sea area of around 37,800 km² (95.24%) and a land area of 1,251.02 km². The fishing community in Alo Village utilizes fishery resources as their main source of life. especially the coastal community of Alo village which is dominated by fishermen who are classified as labor fishermen or small fishermen. Fishing communities are small groups of people living in coastal areas whose main livelihood is utilizing the natural resources found in the ocean, whether in the form of fish, shrimp, seaweed, shellfish, coral reefs and other marine wealth. To determine the level of welfare of the fishing community in Alo Village. The type of research method used in this research is census research using descriptive analysis. So it can be concluded that the level of welfare of the fishing community in Alo Village, Rainis District, Talaud Islands District, with the number of respondents representing as many as 30 respondents was categorized as quite prosperous or moderate with a percentage of 66.67% and a score of 13. Keywords: Alo Village, Welfare, Income, Expenditures, education. Abstrak Kabupaten Kepulauan Talaud merupakan daerah bahari dengan luas lautnya sekitar 37.800 km² (95,24%) dan luas wilayah daratan 1.251,02 km². Masyarakat nelayan di Desa Alo memanfaatkan sumberdaya perikanan sebagai sumber kehidupan utama. khususnya masyarakat pesisir desa Alo yang di dominasi oleh nelayan yang tergolong nelayan buruh atau nelayan – nelayan kecil. Masyarakat nelayan yaitu kelompok kecil masyarakat yang tinggal di wilayah pesisir dengan mata pencaharian utama adalah memanfaatkan sumberdaya alam yang terdapat di dalam lautan, baik itu berupa ikan, udang, rumput laut, kerang- kerangan, terumbu karang dan hasil kekayaan laut lainnya. Untuk mengetahui tingkat kesejahteraan masyarakat nelayan Desa Alo. Jenis metode penelitian yang digunakan dalam penelitian ini adalah penelitian sensus dengan menggunakan analisis deskriptif. Maka dapat disimpulkan bahwa tingkat kesejahteraan masyarakat nelayan di Desa Alo Kecamatan Rainis Kebupatan Kepulauan Talaud, dengan jumlah responden yang mewakili sebanyak 30 responden dikategorikan cukup sejahtera atau sedang dengan persentase 66,67% dan nilai skor 13. Kata kunci: Desa Alo, Kesejahteraan, Pendapatan, Pengeluaran, pendidikan.